The effectiveness of peer educators and guidance counselling teachers to the knowledge of reproductive health - Niken Meilani; Nanik Setiyawati (Intelektual Pustaka Media Utama, 2022)
Adolescence is the most vulnerable period to reproductive health problems. These problems include early pregnancy, unsafe abortion, sexually infections transmitted (STIs) including the human immunodeficiency virus (HIV), sexual abuse. Access for sexuality education and reproductive health services to comprehensive and youth-friendly was limited. This study aims to determine the effectiveness of peer educators and guidance and counselling teachers in adolescent reproductive health level of knowledge. This is a quantitative study with a quasi-experimental nonequivalent control group design with treatment groups using peer educators and teacher as control groups. The sample size was 70 respondents. Data was collected by questionnaire that already had validity and reliability test. Data analysis used univariate, t-test and logistic regression. The results of this study showed that the provision of information was more effective through guidance conselling teachers (p=0.000, exp B=14.5). This study recommends that improve adolescents’ reproductive knowledge need to optimize the role of guidance and counseling teachers in providing information.